Divine attributes in al-Kashshaf by al-Zamakshari (538H) and Mafatih al-Ghayb by al-Razi (606H): Explanation and criticism / Kharsan Mohamed Abdullah - Kharsan Mohamed , Abdullah (2015)
This study is based on the issue of divine attributes between two scholars of speech, Al Zamakshari and Fakhr Al Razi through the the interpretation entitled: (Divine Attributes In Al-Kashaf By Al-Zamakshari (538h) And Mafatih Al-Ghayb By Al-Razi (606h),(Explanation And Criticism), I have selected these two books Al Kashaf and Mafatih Al Ghayb because Al Zamakshari is considered to be one of the important source of the Mu'tazila and those who followed the same way from the Khawarij and Shiites and those who agree with interpretation of some divine attributes. On the other hand, Al Razi is considered to be a great source for those who interpret the divine attributes, he formatted it in his own way which exceeded the previous scholars who came before him in term of interpretations. Moreover, Al Razi is considered to be an Encyclopedia in knowing the beliefs of Madhadbs and the answer for them. The importance of this research is in term of the topic of the attributes because it's the most important topic in the Islamic faith since it is related to the faith in Allah Almighty, The term of Allah is understood by its attributes. Therefore, believing in the names and attributes of Allah is the most important requirements and the essence of worshipping Allah Almighty can not be achieved and done except by knowing Allah's names and his attributes. People were divided in attributing Allah Almighty to Múlh Muthbatah, Mufawidah and Mujasimaha and these opinions are still ongoing until today. I used in this study both the inductive and analytical methods and the comparative method as well. The research was divided into an introduction and four chapters and a conclusion. First chapter is an introductory which includes the definition of the research title and interpretation of Al Kashaf for Al Zamakshari and Mafatih Al Ghayb for Al Razi and their methods in interpretation and the impact of Al Zamakshari in Al Razi and their impact on those who came after them. The second chapter is an introductory in the names and attributes, it's divided into three topics. In the first topic I talked about the foundations which the scholars of speech based their opinions of the divine attributes on .In the second topic I talked about the opinions of the people regarding the attributes which based on inductive method, they believe in Ta'weel Tafweed Tashbeeh and Ithbat. In the third topic I discussed the relationship between the attributes and the Allah in the term of unity. Everyone seeks to achieve Tawheed but the concept is different from one madhab to another. For the philosophers have their own concept , Mu'tazilah have their own concept, Ash'ari have their own concept, the people of proof have their concept and on these basis they judge the attributes and here Al Razi specialized in his saying of renewing the acts of Allah Almighty. Third and fourth chapters, They are the main chapters in the research I talked in them about the Dhateeah and Fi'leeah attributes in Al Kashaf and Mafatih AlGayb. I compared between them in term of definition, proof, what they prove and what they deny and what they agree upon like attributing the Fi'leeah and dhateeh acts according to their madhab. In addition, a saying of Al Razi where he proves Allah love and cunning attributes. As well as I mentioned their sayings of their madhabs in brief explaining the attributes and then my saying as a researcher in these attributes. I concluded the reaseach with the results I mentioned at the end and all praise be to Allah, the Lord of the Worlds.